RETRACTION Nurkadri, N., Akhmad, I., Suharta, A.., Pujianto, D., Laksana, A. A. N. P., Siong, N. U., Hafiz, E., Setyawan, H., Hamsyah, K., Sabariah, S., Rufi’i, R., Shidiq, A. A. P., & Syafitra, V. (2024). El papel de la tecnología digital inteligente para llevar puesta en la medición del VO2MAX para apoyar el rendimiento de los atletas y la salud pública (The role of digital smart wearable technology in measuring VO2MAX to support athlete performance and public health). Retos, 61, 1534–1545. https://doi.org/10.47197/retos.v61.110327 - RETOS, RETOS (Retos, 2025)
Nurkadri, N., Akhmad, I., Suharta, A.., Pujianto, D., Laksana, A. A. N. P., Siong, N. U., Hafiz, E., Setyawan, H., Hamsyah, K., Sabariah, S., Rufi’i, R., Shidiq, A. A. P., & Syafitra, V. (2024). El papel de la tecnología digital inteligente para llevar puesta en la medición del VO2MAX para apoyar el rendimiento de los atletas y la salud pública (The role of digital smart wearable technology in measuring VO2MAX to support athlete performance and public health). Retos, 61, 1534–1545. https://doi.org/10.47197/retos.v61.110327 Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that the authorship of the article has been manipulated. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were needed. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. Likewise, a large number of citations and references were manipulated. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI. Authors in the Word document of the article submitted for review: 2 Authors in the published PDF with modified authors: 13 Differences between the authors between both moments: +11 (Additions: Imran Akhmad, Asep Suharta, Dian Pujianto, Anak Agung Ngurah Putra Laksana, Nguang Ung Siong, Eliza Hafiz, Khairul Hamsyah, Sabariah, Rufi’i, Abdul Aziz Purnomo Shidiq, Viony Syafitra)